2005
DOI: 10.1152/jn.00850.2004
|View full text |Cite
|
Sign up to set email alerts
|

Complex Expression and Localization of Inactivating Kv Channels in Cultured Hippocampal Astrocytes

Abstract: .Voltage-gated potassium channels are well established as critical for setting action potential frequency, membrane potential, and neurotransmitter release in neurons. However, their role in the "nonexcitable" glial cell type is yet to be fully understood. We used whole cell current kinetics, pharmacology, immunocytochemistry, and RT-PCR to characterize A-type current in hippocampal astrocyte cultures to better understand its function. Pharmacological analysis suggests that ϳ70, 10, and Ͻ5% of total A current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 65 publications
(28 reference statements)
2
23
1
Order By: Relevance
“…3). This is compatible with the presence of 2P-domain K 1 channels (for review see Goldstein et al, 2001) or Kv channels (Bekar et al, 2005). Gnatenco et al (2002) have shown that mRNA for TASK-1, TASK-3, and TREK-2 was present in cultured cortical astrocytes.…”
Section: Maintenance Of a Hyperpolarized Membrane Potentialsupporting
confidence: 64%
“…3). This is compatible with the presence of 2P-domain K 1 channels (for review see Goldstein et al, 2001) or Kv channels (Bekar et al, 2005). Gnatenco et al (2002) have shown that mRNA for TASK-1, TASK-3, and TREK-2 was present in cultured cortical astrocytes.…”
Section: Maintenance Of a Hyperpolarized Membrane Potentialsupporting
confidence: 64%
“…Other A-type channel subunits that are highly expressed are K v 4.2, K v 4.3, and Kv3.3. K v 4.2 and 4.3 have been found in neurons (Tsaur et al, 1997) and cultured astrocytes (Bekar et al, 2005), but never previously in oligodendrocyte lineage cells. Kv3.3 has been found in neurons, particularly in the cerebellum and brainstem (Chang et al, 2007), but not in glial cells.…”
Section: Ion Channelsmentioning
confidence: 83%
“…Strong dendritic expression of K V 4.2, which may be based on dendritic localization of K V 4.2 mRNA [22], has also been found in hippocampal and cortical pyramidal cells [37]. None of the neuropil staining of K V 4.2 in intralaminar nuclei results from channel expression in glia cells, although the expression of K V 4.2 in hippocampal reactive glia cells in epilepsyassociated focal lesions [1] and K V 4.3 in hippocampal astrocytes [2] has been found.…”
Section: Expression Profile Of K V Channel Subunits Producing Transiementioning
confidence: 98%